Analysis of Factors Affecting Increasing the Effectiveness of MSMEs in the Covid-19 Pandemic Period and the New Normal Era (Case Study on MSMEs Champion in Bogor Regency - Melly Supiyati; Indapurnahayu Indapurnahayu; Renea Shinta Aminda (Universitas muhammadiyah malang, 2021)
ABSTRACT The Covid-19 pandemic has caused many problems, one of which is the economic slowdown. In this case, the sector that has the most impact is the Micro, Small and Medium Enterprises (UMKM) sector, where restrictions on community activities during the Covid-19 pandemic have caused a decline in income, making MSMEs need to limit their production. With reduced production, MSMEs do not involve much labor and participate in online markets to market their products. Of course, this difficult condition also affects the capital of MSMEs themselves. MSME actors also need to develop strategies for business continuity and adapt them to the conditions of the Covid-19 pandemic. The purpose of this study was to analyze the MSME Champion in Bogor Regency, on the factors that influence the MSME strategy towards increasing the effectiveness of MSMEs during the Covid-19 pandemic and in the new normal era. The type of research that will be used is descriptive qualitative. This study uses a quantitative approach with a sample of 72 respondents with the sampling technique used is the non-probability sampling method, namely by purposive sampling. The results of the study indicate that the workforce has no effect on the effectiveness of MSMEs. MSME business actors who access online markets also have no effect on the effectiveness of MSMEs. Meanwhile, capital has an influence on the effectiveness of MSMEs. For this reason, capital assistance or easy access to capital from the government and other financial institutions is very helpful for MSME business actors in increasing the effectiveness of MSMEs during the current pandemic. Keywords: MSMEs, Labor, Capital, Online Market